2017
DOI: 10.1371/journal.pone.0186873
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylated Fgf3 is a potential biomarker for early detection of oral cancer in mice treated with the tobacco carcinogen dibenzo[def,p]chrysene

Abstract: Genetic and epigenetic alterations observed at end stage OSCC formation could be considered as a consequence of cancer development and thus changes in normal or premalignant tissues which had been exposed to oral carcinogens such as Dibenzo[def,p]chrysene (DBP) may better serve as predictive biomarkers of disease development. Many types of DNA damage can induce epigenetic changes which can occur early and in the absence of evident morphological abnormalities. Therefore we used ERRBS to generate genome-scale, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…In PCa that would be discerning low-risk vs high-risk disease or identifying small but aggressive tumours and determining most appropriate therapeutic options. In addition, epigenetic changes are known to manifest early in tumourigenesis, making them useful for both diagnosis and prognosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PCa that would be discerning low-risk vs high-risk disease or identifying small but aggressive tumours and determining most appropriate therapeutic options. In addition, epigenetic changes are known to manifest early in tumourigenesis, making them useful for both diagnosis and prognosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…DBP also resulted in a significant upregulation of several inflammatory-related genes in the mouse oral tissue (11). Moreover, we showed that hypomethylation of Fgf3 is a potential biomarker for early detection of OSCC in mice treated with DBP (12). Fgf3 is among a large fibroblast growth factor superfamily genes, which are involved in numerous biological activities, including cell survival and regulation of epithelial-mesenchymal transition (EMT) pathway (13)(14)(15).…”
Section: Introductionmentioning
confidence: 90%
“…Dibenzo[ def , p ]chrysene (DBP) is the most potent carcinogenic polycyclic aromatic hydrocarbons (PAH) found in tobacco that induces oral cancer in animal models [19]. Mice treated with DBP developed maximum DNA damage, which included 30 and 48 differentially methylated CpG sites [20]. These methylated sites were mapped to genes known to be involved in cancer-related pathways.…”
Section: Epigenetic Carcinogenic Changes In Oscc Induced By Tobaccomentioning
confidence: 99%
“…The most significant finding was intronic hypomethylation of FGF3 (correlating with gain of expression), observed in an early stage of the OSCC development but not evident in control oral mucosa not treated with DBP, and also intronic hypermethylation of VAMP3 that was inversely correlated with its expression. These results indicate that tobacco carcinogen DBP plays an essential role in oral carcinogenesis induced by tobacco and that it affects methylation with the gene body, changing expression patterns and this epigenetic changes may serve as a potential biomarker for early detection of OSCC [20].…”
Section: Epigenetic Carcinogenic Changes In Oscc Induced By Tobaccomentioning
confidence: 99%